Synthesis of cobalt complex and application of cobalt complex in detection of copper ions and uranyl ions and degradation of methylene blue dye
By preparing cobalt complexes, the problem of rapid detection of divalent copper ions and uranyl root ions in the prior art and the treatment of methylene blue dye wastewater is solved, and rapid detection and efficient degradation are achieved, which is suitable for environmental monitoring and industrial production.
Patent Information
- Application Number
- CN202411339398.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
AI Technical Summary
The prior art cannot quickly and accurately detect divalent copper ions and divalent uranyl root ions, and traditional methods treat methylene blue dye wastewater complex and incomplete, resulting in environmental pollution and health hazards.
Prepare a cobalt complex using 4,4'-bis(2-methyl-1-imidazolyl) diphenyl ether and 2,5-dihydroxyterephthalic acid and cobalt nitrate hexahydrate, It has fluorescence recognition function, can efficiently detect divalent copper ions and uranyl root ions, and has the ability to photodegrade methylene blue dye.
It realizes rapid, quantitative and sensitive detection of divalent copper ions and uranyl root ions, as well as efficient and thorough degradation of methylene blue dye wastewater. It has simple process and low cost, and is suitable for industrial production and environmental monitoring.
Smart Images

Figure CN119161394A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of cation detection and dye degradation, and specifically relates to the preparation of a cobalt complex with 4,4'-di(2-methyl-1-imidazolyl)biphenyl ether (BMIOPE) and 2,5-dihydroxyterephthalic acid (H2DOBDC) as ligands and a method for detecting divalent copper ions (Cu 2+ ) and uranyl ions (UO2 2+ ) and application of degraded methylene blue dye (MB). Background Art
[0002] Copper, as a heavy metal element widely present in nature, is an important factor affecting copper enzyme proteins in organisms and has important physiological effects on the human body. Copper deficiency can lead to anemia, leukopenia, degeneration of the central nervous system, low blood iron, low blood copper, low serum protein syndrome, and even liver and kidney damage. Excess copper will accumulate in organs, causing adverse effects such as memory loss and inattention. Traditional means of detecting copper ions are mainly atomic absorption spectrometry, electrochemical sensing, spectrophotometry, etc. These methods are often complicated to operate, have cumbersome steps, take a long time to detect, and cannot produce results in real time. Therefore, it is necessary to explore a method that can quickly, conveniently and accurately detect divalent copper ions (Cu 2+ ) technology has far-reaching development prospects.
[0003] In today's era of rapid development of nuclear industry, uranium is widely used. As an energy source, uranium has a half-life of 4.5×10 9 In water, uranyl ions (UO2 2+ ) exists in the form of UO2 2+ Uranyl ions are highly radioactive and harmful radioactive metal ions. When humans ingest excessive amounts of uranyl ions, it can cause necrosis of glomerular cells and atrophy of the renal tubular walls, thereby causing a decline in the kidney's ability to filter blood impurities. In addition to harming the blood filtration system, if too many uranyl ions accumulate in the human body, it can also lead to respiratory diseases, skin diseases, neurological disorders, chromosome damage, and decreased immune function. Therefore, it is necessary to explore a method that can quickly, conveniently, and accurately detect divalent uranyl ions (UO2 2+ ) technology has far-reaching development prospects.
[0004] my country is a large country of light industry. With the rapid development of my country's economy, the output of textile industry is also expanding, and the pollution scale of textile dyes is also expanding sharply. When the treatment of methylene blue dye wastewater is not up to standard and is discharged into natural water bodies, due to the light absorption of methylene blue, it will compete for the oxygen present in natural water bodies, causing the natural water bodies to consume a large amount of oxygen, thereby destroying the self-purification function of the water body, causing the death of animals and plants in the water, and destroying the natural ecological environment. In addition, methylene blue dye waste liquid also contains sensitizing and toxic components, which are very harmful to the human body. The traditional adsorption precipitation method for treating methylene blue dye wastewater is complicated, and the treatment is not thorough enough. So it is urgent to find a method for efficiently treating methylene blue dye wastewater.
[0005] Metal-organic framework materials are a new type of self-assembled inorganic-organic hybrid microporous materials with the characteristics of diverse structures, high porosity, and large specific surface area. By selecting different metal ions and organic ligands with different structures, the target analyte molecules can be adsorbed by the metal-organic framework materials, thereby achieving pre-concentration of the analyte and significantly improving the sensitivity of the analysis. Thanks to their high specific surface area, adjustable pore size, and diverse active sites, metal-organic framework materials have shown great application potential in the field of photocatalytic degradation in recent years. In addition, many metal-organic framework materials have good stability, which gives them a long service life in practical applications.
[0006] At present, a series of fluorescent probe complexes have been reported, but the functions of a certain metal complex are relatively single, and the reports on its fluorescence detection are mainly focused on the detection of a single substance, with a narrow range of applications. Complexes with fluorescence detection and photodegradation have been reported in large numbers, but there are very few reports on complexes that can simultaneously detect divalent copper ions and divalent uranyl ions and have obvious photodegradation properties. Summary of the invention
[0007] The present invention aims to provide a cobalt complex capable of simultaneously detecting divalent copper ions and uranyl ions and degrading methylene blue dye wastewater and a preparation method thereof. The present invention selects 4,4′-di(2-methyl-1-imidazolyl)biphenyl ether, 2,5-dihydroxyterephthalic acid and cobalt nitrate hexahydrate to construct a cobalt complex. The cobalt complex has a function of fluorescent recognition of divalent copper ions and uranyl ions, and can efficiently detect trace copper ions and uranyl ions contained in an aqueous solution. At the same time, the cobalt complex can efficiently degrade a methylene blue wastewater solution. Finally, the cobalt complex has a simple synthesis process, low cost, high yield, good reproducibility, easy separation, can be applied to industrial large-scale production, and has potential application prospects in the fields of environmental monitoring, life sciences and pollutant degradation.
[0008] The chemical formula of the cobalt complex involved in the present invention that can simultaneously detect divalent copper ions and uranyl ions and degrade methylene blue dye wastewater is: [Co(DOBDC)(BMIOPE)], wherein H2DOBDC=2,5-dihydroxyterephthalic acid, BMIOPE=4,4'-di(2-methyl-1-imidazolyl)biphenyl ether. The structural formula of BMIOPE and H2DHBDC is as follows:
[0009]
[0010] Furthermore, the structural formula of the cobalt complex is:
[0011]
[0012] The cobalt complex involved in the present invention, which can simultaneously detect divalent copper ions and uranyl ions and degrade methylene blue dye wastewater, has the following basic structural parameters:
[0013] The crystal of the cobalt complex of the present invention belongs to the orthorhombic system, its space group is P212121, and the unit cell parameters are α=90°, β=90°, γ=90°, The smallest asymmetric unit of the cobalt complex consists of two different cobalt ions (Co1 and Co2), two different BMIOPE ligands and two different DOBDC 2- Anion composition. Cobalt ions are bound to two nitrogen atoms in two different BMIOPE ligands and two different DOBDC 2- The two oxygen atoms in the ligand coordinate to form a distorted CoN2O2 tetrahedral geometry ( Figure 1 ). Adjacent cobalt ions are bound by BMIOPE ligands and DOBDC 2- The ligands are connected to each other to form a two-dimensional planar structure ( Figure 2 ). In this two-dimensional plane structure, there is a quadrilateral cavity. Due to the large size of this quadrilateral cavity, adjacent two-dimensional planes intersect with each other to form a three-dimensional structure ( Figure 3 ).
[0014] The preparation method of the cobalt complex involved in the present invention comprises the following steps:
[0015] (1) 4,4′-di(2-methyl-1-imidazolyl)biphenyl ether, 2,5-dihydroxyterephthalic acid, and cobalt nitrate hexahydrate were mixed in a molar ratio of 1:1:1, and an aqueous solution was added. After mixing, the mixture was placed in a 10 ml polytetrafluoroethylene liner and subjected to ultrasonic oscillation to obtain a mixed solution;
[0016] (2) transferring the 10 ml polytetrafluoroethylene liner into a 50 ml reactor, heating from room temperature to 100° C. within two hours and reacting at this temperature for 72 hours under autogenous pressure;
[0017] (3) After the reaction is completed, the product is cooled to 40°C within 30 hours and finally cooled to room temperature.
[0018] Furthermore, the present invention provides the use of the above cobalt complex for detecting divalent copper ions and uranyl ions and degrading methylene blue dye in aqueous solution, which can be used to monitor divalent copper ions and uranyl ions in the environment and to degrade methylene blue dye in aqueous solution as a photodegradation catalyst.
[0019] The invention has the advantages that the preparation method has simple process, high yield, easy separation and good reproducibility, can obtain single crystal form and high-purity materials, and is easy to industrialize; the cobalt complex has a fluorescence recognition function for divalent copper ions and uranyl ions, can be used for detecting trace divalent copper ions and uranyl ions in aqueous solution, and compared with the traditional detection method, the method has the advantages of quantitative, rapid, sensitive, efficient, simple operation and the like; the cobalt complex can degrade methylene blue dye in aqueous solution, and compared with the traditional treatment method, the method has the advantages of high efficiency, thorough reaction and no secondary pollution.
[0020] Figure content
[0021] Figure 1 Figure 1 is a diagram of the coordination environment of the cobalt ion of the cobalt complex of the present invention.
[0022] Figure 2 It is a two-dimensional planar structure diagram of the cobalt complex of the present invention.
[0023] Figure 3 3D structure diagram of the cobalt complex of the present invention.
[0024] Figure 4 The figure is the powder XRD pattern of the cobalt complex of the present invention.
[0025] Figure 5 The thermogravimetric diagram of the cobalt complex of the present invention.
[0026] Figure 6 This is a solid fluorescence image of the cobalt complex of the present invention.
[0027] Figure 7 The graph is a fluorescence intensity graph of the cobalt complex of the present invention in aqueous solutions containing uranyl ions at different concentrations.
[0028] Figure 8 It is a linear fitting spectrum of the fluorescence peak ratio of the cobalt complex of the present invention and the uranyl ion concentration.
[0029] Fig. 9The graph is a fluorescence intensity graph of the cobalt complex of the present invention in aqueous solutions containing copper ions at different concentrations.
[0030] Fig.10 It is a linear fitting spectrum of the fluorescence peak ratio of the cobalt complex of the present invention and the copper ion concentration.
[0031] Fig.11 This is a diagram showing the photocatalytic degradation of methylene blue dye by the cobalt complex of the present invention.
[0032] Fig.12 It is the infrared spectrum of the cobalt complex of the present invention. DETAILED DESCRIPTION
[0033] In order to better understand the present invention, the content of the present invention is further described below in conjunction with implementation examples, but the content of the present invention is not limited to the following embodiments.
[0034] Example 1: Synthesis of complex
[0035] (1) 4,4′-di(2-methyl-1-imidazolyl)biphenyl ether (0.05 mmol), 2,5-dihydroxyterephthalic acid (0.05 mmol), and cobalt nitrate hexahydrate (0.05 mmol) were mixed in a molar ratio of 1:1:1, and then an aqueous solution (2.5 ml) was added. After mixing, the mixture was placed in a 10 ml polytetrafluoroethylene liner and subjected to ultrasonic oscillation to obtain a mixed solution;
[0036] (2) transferring the 10 ml polytetrafluoroethylene liner into a 50 ml reactor, heating from room temperature to 100° C. within two hours and reacting at this temperature for 72 hours under autogenous pressure, cooling the product to 40° C. within 30 hours after the reaction, and finally cooling to room temperature;
[0037] (3) After the reaction in step (2) is completed, the precipitate obtained by the reaction is washed with water and ethanol in sequence, and dried to obtain red block crystals, which are the cobalt complex, with a yield of 72.3%.
[0038] Experimental Example 1: Crystal structure determination
[0039] Single crystals of appropriate size were selected using a microscope and analyzed at room temperature using a Siemens (Bruker) SMART CCD diffractometer (graphite monochromator, Mo-Ka, ) to collect diffraction data. Diffraction data were corrected for absorption using the SADABS program. Data reduction and structure analysis were performed using SAINT and SHELXTL programs, respectively. The least squares method was used to determine the coordinates of all non-hydrogen atoms, and the positions of hydrogen atoms were obtained using the theoretical hydrogenation method. The crystal structure was refined using the least squares method.
[0040] The cobalt complex synthesized in Example 1 crystallizes in the orthorhombic system with a space group of P212121. The smallest asymmetric unit of the cobalt complex consists of two different cobalt ions (Co1 and Co2), two different BMIOPE ligands and two different DOBDC 2- Anion composition. Figure 1 As shown, the cobalt ion binds to two nitrogen atoms in two different BMIOPE ligands and two different DOBDC 2- The two oxygen atoms in the ligands coordinate to form a distorted CoN2O2 tetrahedral configuration. The adjacent cobalt ions were ionized by BMIOPE and DOBDC. 2- The ligands are connected to form a two-dimensional planar structure ( Figure 2 There are large quadrilateral cavities in this two-dimensional planar structure. Due to the large size of these quadrilateral cavities, adjacent two-dimensional planes intersect with each other to form a three-dimensional structure ( Figure 3 ).
[0041] Experimental Example 2: Powder XRD
[0042] The powder X-ray diffraction data of the cobalt complex synthesized in Example 1 are basically consistent with the theoretical diffraction peak data obtained by single crystal data simulation, indicating that the prepared cobalt complex crystal has a high phase purity. Figure 4 shown.
[0043] Experimental Example 3: Thermogravimetric Analysis
[0044] The cobalt complex synthesized in Example 1 was subjected to thermogravimetric analysis using a thermogravimetric analyzer, and the obtained Figure 5 The cobalt complex of the present invention is stable below 270°C, and when the temperature exceeds 270°C, the mass begins to decrease rapidly, which is mainly caused by the thermal decomposition of 4,4′-di(2-methyl-1-imidazolyl)biphenyl ether and 2,5-dihydroxyterephthalic acid.
[0045] Experimental Example 4: Solid Fluorescence Properties
[0046] The solid fluorescence properties of the cobalt complex synthesized in Example 1 were tested using a fluorescence spectrometer, and the results were Figure 6 The solid fluorescence diagram shown shows that the excitation peak of the cobalt complex is 240 nanometers, and the emission peak is 360 nanometers.
[0047] Experimental Example 5: Fluorescence Detection of Uranyl Ions
[0048] By measuring the fluorescence spectrum of the cobalt complex synthesized in Example 1 in aqueous solutions of uranyl ions at different concentrations, we can obtain Figure 7As shown in the fluorescence emission spectrum, it can be seen that the fluorescence intensity gradually decreases with the increase of uranyl ion concentration, showing an obvious fluorescence quenching effect. The cobalt complex can be used to detect trace uranyl ions in aqueous solution.
[0049] Using the Stern-Volmer equation (I0 / I=1+K sv [M]) calculated the relationship between the relative change ratio of fluorescence intensity (I0 / I) and the concentration of uranyl ions, and plotted Figure 8 The SV graph shown shows that the two are linearly related in the low concentration range, and the quenching constant K sv 1.81×10 4 .
[0050] Experimental Example 6: Copper Ion Fluorescence Detection
[0051] By measuring the fluorescence spectra of the cobalt complex synthesized in Example 1 in aqueous copper ion solutions of different concentrations, we can obtain Fig. 9 From the fluorescence emission spectrum shown, it can be seen that the fluorescence intensity gradually decreases with the increase of copper ion concentration, showing an obvious fluorescence quenching effect, indicating that the cobalt complex can detect copper ions in aqueous solution.
[0052] The relationship between the relative change ratio of fluorescence intensity (I0 / I) and copper ion concentration was calculated using the Stern-Volmer equation, and the Fig.10 The SV graph shown shows that the two are linearly related in the low concentration range, and the quenching constant K sv is 3.19×10 4 .
[0053] Experimental Example 7: Photodegradation of methylene blue dye
[0054] 30 mg of the cobalt complex synthesized in Example 1 was weighed and added to 50 ml of a methylene blue aqueous solution (10 mg / L), and then 5 μL of hydrogen peroxide was added. The mixture was stirred in the dark for 30 minutes to allow the surface of the cobalt complex to reach an adsorption-desorption equilibrium. The mixture was then irradiated with a visible light while stirring at an intensity of 300 watts, room temperature, and a pH of about 7. 1 ml of the methylene blue aqueous solution was taken every 10 minutes, and the absorbance change was immediately tested. The photodegradation results showed that the degradation rate of the cobalt complex for methylene blue in 60 minutes was 97.9% (as shown in Figure 2). Fig.11 ).
Claims
1. A cobalt complex capable of simultaneously detecting divalent copper ions and uranyl ions and degrading methylene blue dye wastewater, characterized in that: Its chemical formula is [Co(DOBDC)(BMIOPE)], wherein BMIOPE = 4,4′-di(2-methyl-1-imidazolyl)biphenyl ether, H2DOBDC = 2,5-dihydroxyterephthalic acid; the cobalt complex belongs to the orthorhombic system, its space group is P212121, and the unit cell parameters are α=90°, β=90°, γ=90°, Adjacent cobalt ions are separated by BMIOPE and DOBDC 2- They are interconnected to form a two-dimensional plane structure, and adjacent two-dimensional planes are intertwined to eventually form a three-dimensional structure.
2. The method for preparing a cobalt complex according to claim 1, characterized in that: The steps are as follows: under sealed conditions, 4,4′-di(2-methyl-1-imidazolyl)biphenyl ether, 2,5-dihydroxyterephthalic acid, and cobalt nitrate hexahydrate are mixed, and a target cobalt complex is obtained through a hydrothermal reaction in an aqueous solution, wherein the molar ratio of 4,4′-di(2-methyl-1-imidazolyl)biphenyl ether, 2,5-dihydroxyterephthalic acid, and cobalt nitrate hexahydrate is 1:1:1, and every 0.05 mmol of cobalt nitrate hexahydrate corresponds to 2.5 ml of deionized water. The thermal reaction conditions are 100° C. and the reaction time is three days.
3. Use of the cobalt complex as claimed in claim 1 or the cobalt complex prepared by the method as claimed in claim 2 as a fluorescent probe in the field of detecting divalent copper ions and uranyl ions.
4. A use according to claim 3, characterized in that The linear fitting curve equation of the relative change ratio of the fluorescence intensity of the cobalt complex and the concentration of divalent copper ions is: I0 / I=31950[Cu 2+ ]+0.9962; the linear fitting curve equation of the relative change ratio of the fluorescence intensity of the cobalt complex and the concentration of uranyl ions is: I0 / I=18170[UO2 2+ ]+0.9999.
5. Use of the cobalt complex as claimed in claim 1 or the cobalt complex prepared by the method as claimed in claim 2 in the field of photocatalytic degradation of dye molecules.
6. The use according to claim 5, characterized in that: The dye molecule is methylene blue.
